Heterogeneity of Players and Aggregate Effort in Contests. Issue 4 (18th October 2013) - Ryvkin, Dmitry
Abstract : We explore the systematic effects of variation in players' heterogeneity on aggregate effort in contests. We show that if costs of effort are convex, a mean‐preserving increase in the variation of players' abilities can lead to an increase or decrease in aggregate effort, both in contests of complete and incomplete information, depending on the curvature of the effort cost function. Specifically, if effort costs are not too steep, aggregate effort increases in ability variation, whereas if effort costs are sufficiently steep, aggregate effort decreases in ability variation.